2017
DOI: 10.3390/soc7030023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heart Rate Levels in the Intergenerational Transmission of Crime

Abstract: Abstract:Several prospective multigenerational studies have shown that crime runs in the family, while empirical research on the biological causes of crime has also established that low heart rate is related to antisocial behavior. This study examines whether the intergenerational transmission of crime is moderated or mediated by a low heart rate of the son. Prospectively collected conviction data on 794 men from three consecutive generations of the Dutch Transfive dataset is used. Heart rates were measured ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(64 reference statements)
1
1
0
Order By: Relevance
“…These studies generally show that antisocial outcomes are found only among children with a combination of psychosocial risk and low RHR. More comparably with the present research, Van de Weijer et al (2017) in the Netherlands showed that there was intergenerational transmission of convictions for violence only among men with low RHR at Age 18. Van Hazebroek et al (2019) completed a systematic review of biopsychosocial interaction studies and also concluded that it was the combination of social adversity and low RHR that was related to antisocial outcomes.…”
Section: Introductionsupporting
confidence: 89%
“…These studies generally show that antisocial outcomes are found only among children with a combination of psychosocial risk and low RHR. More comparably with the present research, Van de Weijer et al (2017) in the Netherlands showed that there was intergenerational transmission of convictions for violence only among men with low RHR at Age 18. Van Hazebroek et al (2019) completed a systematic review of biopsychosocial interaction studies and also concluded that it was the combination of social adversity and low RHR that was related to antisocial outcomes.…”
Section: Introductionsupporting
confidence: 89%
“…One study found that higher RHR protected subjects against developing proactive aggression in the context of community violence victimization (Scarpa, Tanaka, & Haden, 2008). In contrast, interactions between RHR and fathers' criminal history were not associated with delinquent behavior (van de Weijer, de Jong, Bijleveld, Blokland, & Raine, 2017).…”
Section: General Ans Functioningmentioning
confidence: 99%